Peer-coaching with health care professionals: What is the current status of the literature and what are the key components necessary in peer-coaching? A scoping review - Schwellnus, Heidi; Carnahan, Heather (Medical teacher, 2014)
Background: Peer-coaching has been used within the education field to successfully transfer a high percentage of knowledge into practice. In recent years, within health care, it has been the subject of interest as a method of both student training and staff continuing education as well as a format for knowledge translation. Aims: To review the literature from health care training and education to determine the nature and use of peer-coaching. Method: Due to the status of the literature, a scoping review methodology was followed. From a total of 137 articles, 16 were found to fit the inclusion criteria and were further reviewed. Results: The review highlights the state of the literature concerning peer-coaching within health care and discusses key aspects of the peer-coaching relationship that are necessary for success. Conclusions: Most research is being conducted in the domains of nursing and medicine within North America. The number of studies has increased in frequency over the past 10 years. Interest in developing the potential of peer-coaching in both health care student education and continuing clinical education of health care professionals has grown. Future directions for research in this quickly developing area are included.